2016
DOI: 10.1080/02508281.2016.1192237
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, drugs, and tourism: tourists’ and shamans’ experiences of ayahuasca in Iquitos, Peru

Abstract: This study critically evaluates the complex inter space of spirituality, drugs, and tourism through tourists' and shamans' accounts of ayahuasca tourism in Iquitos, Peru. Ayahuasca is a hallucinogenic beverage traditionally consumed for spiritual and health purposes. Using microethnography, one of the researchers was immersed for one month in the tourism experience of ayahuasca. The findings reveal the ambivalent nature of tourists' experiences and the changing meaning and practices of ayahuasca. Tourists' enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
(78 reference statements)
0
14
0
3
Order By: Relevance
“…Spirituality is also seen as a cultural endeavor or resource ( (Fonneland, 2013;Gezon, 2017) with positive outcomes but also negative on local culture as seen with the Aboriginal community on Smith, Scherrer, and Dowling (2009) study. As in our introduction, spirituality is considered a more individual experience where a search for a connection with something bigger or pursuing meaning on life is sought ((Moal-Ulvoas, 2017;Prayag, Mura, Hall & Fontaine, 2016;Singh, 2009;Willson, McIntosh, & Zahra, 2013). The increasing importance of spirituality on tourism is also clear on Barkathunnisha, Lee and Price (2016) study where it is explored a possible model to include it in tourism education.…”
Section: Authors Date Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spirituality is also seen as a cultural endeavor or resource ( (Fonneland, 2013;Gezon, 2017) with positive outcomes but also negative on local culture as seen with the Aboriginal community on Smith, Scherrer, and Dowling (2009) study. As in our introduction, spirituality is considered a more individual experience where a search for a connection with something bigger or pursuing meaning on life is sought ((Moal-Ulvoas, 2017;Prayag, Mura, Hall & Fontaine, 2016;Singh, 2009;Willson, McIntosh, & Zahra, 2013). The increasing importance of spirituality on tourism is also clear on Barkathunnisha, Lee and Price (2016) study where it is explored a possible model to include it in tourism education.…”
Section: Authors Date Resultsmentioning
confidence: 99%
“…The studies followed mostly a qualitative approach which is not surprising since spirituality is a complex construct, aligned with personal experiences that need a more in-depth and individual methodology to be understood. Results showed that tourism experiences can be or can lead to spiritual enrichment (Cheer, Belhassen & Kujaw, 2017;Moal-Ulvoas, 2017;Prayag, Mura, Hall & Fontaine, 2016;Singh, 2009;Willson, McIntosh & Zahra, 2013). Spirituality is also seen as a cultural endeavor or resource ( (Fonneland, 2013;Gezon, 2017) with positive outcomes but also negative on local culture as seen with the Aboriginal community on Smith, Scherrer, and Dowling (2009) study.…”
Section: Authors Date Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to suggest that mental and imaginary experiences cannot be profoundly meaningful, but just that they hold little weight in the eyes of Westerners embedded within non-supernatural cosmologies (Philip, 2003;Uriely & Belhassen, 2005). Troublingly though, drinking ayahuasca and adopting indigenous views of a supernatural universe, are acts that invite criticism and stigmatisation from the typical Westerner who regards these practices as tantamount to drug use and the beliefs of the mentally ill (Crocker, Major & Steele., 1998;Goffman, 1963;Prayag, 2015aPrayag, , 2015bWinkelman, 2001). These negative views of psychedelics have existed for hundreds of years in the West, with an on-going critical stance towards those who eat this forbidden fruit (Boyd, 2002;Kehoe, 2000;Siff, 2015).…”
Section: Ayahuasca Tourism: a 'Real' Fairy Talementioning
confidence: 99%
“…Thus, and in the first six months after returning home, all tourists were invited to speak to the author whenever they felt inclined to do so. This resulted in the tourists frequently contacting the author, driven by their concerns about being stigmatised as mentally ill drug users, should they mention their ayahuasca experiences to friends, family, and work colleagues (Prayag, 2015a(Prayag, , 2015bTupper, 2008).…”
Section: Data Collectionmentioning
confidence: 99%